Development of an Indigenous Urdu Glossophobia Scale for University Students in Pakistan - Muhammad Ausama Saleem; Khalid Mahmood (Social Science Review Archives, 2025)
This study aimed to develop and evaluate the psychometric properties of an indigenous Urdu Glossophobia Scale tailored for Pakistani university students. An initial pool of 18 items was constructed based on literature review and expert input. Data were collected from 58 university students, and exploratory factor analysis (EFA) was conducted using principal component analysis with Varimax rotation. The Kaiser-Meyer-Olkin measure (.805) and Bartlett’s test of sphericity (χ² = 500.57, p < .001) confirmed sampling adequacy. EFA revealed a two-factor structure—Cognitive-Affective Concerns and Performance/Interaction Anxiety—explaining 48.52% of the total variance. After the removal of five poorly performing items, the final 13-item scale showed strong internal consistency (α = .934). The findings provide initial support for the scale’s construct validity and reliability. This culturally contextualized tool holds substantial promise for educational, clinical, and psychological assessment in Pakistan.